Gülen on Nature of Knowledge - Zenno Noeralamsyah (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
P This article aim to explore perspective of Fethulleh Gülen about knowledge. The idea that science and religion coalesce in the structure of the universe has been expressed by Western philosophers, that contributed to the almost complete separation of intellectual and scientific activities from religion. In this view of dualism, science and religion both find their apotheosis and its keeping religion and science separating by an unbridgeable chasm. The ontological argument of the idea of giving birth to materialism, which supposes that the nature of existence based on matter. Associated with this, Fethullah Gülen offers a new typical scientific approach that will fuse scientific knowledge and religious beliefs closely associated with spirituality, reconfigures modern understandings of science and faith to relieve the dichotomous presumption of the reason-revelation divide. He is deeply interested in the problematic of the relationship between religion and science, while he does not reject the modern scientific approach, neither does it deify it. The essence of the philosophical thought of Fethullah Gülen (who was otherwise known simply as Hoca Effendi) is that understanding the religious texts and the creeds of Islam should be performed using sufi interpretation and commentary by transmission, without denying current context. In Gülen’s view, religious belief and scientifical reason should be combined, for they are a single truth with two expressions. Therefore, the unification of physics and metaphysics in the nature of knowledge, fundamental concept of bridging science and spirituality, both traditional and modern influences in Gülen's treatment of science will be analyzed in this article, to examine what nature of knowledge is in accordance with Gülen's worldview.